Governing Zakat as a social institution : the Malaysian perspective / Shawal Kaslam - Kaslam, Shawal (Research Management Institute (RMI), 2009)
Zakat is one of the five pillars of Islam and is an ibadah that should be performed by every individual Muslims. A person’s iman is incomplete unless he has performed all the pillars of Islam and a person should not place less importance on any of the pillars. As the Quran says that, it is an obligation of every Muslim, man or woman to give a specific amount of their wealth (as neither ordinary charity nor voluntary alms-giving) – with certain conditions and requirements – to be given to certain categories of people as an ‘equitable redistribution of wealth and income (Quran Surah 9: 71).1 The fundamental principles of Zakat is that zakat is to be established in the fold of Muslim society in an organized manner and under the responsible supervision of the Muslim Government, or of a special Muslim supervisory body appointed by the said Government. The practical functioning of the institution of Zakat must be kept in the highest plane of integrity, courtesy, and loyalty to the Muslim Nation. In this sense, Zakat is more than a personal ibadah; it is also a social institution, which play a pivotal role in socio-economic well-being/affairs of the Muslim Ummah. Zakat has been functioning as an instrument of relieving poverty among the Muslim Ummah and keeping its sanity inspite of its present decadence. This paper examines the practice and implementation of Zakat as a social institution in Malaysia, and its governance in achieving the Muslim socio-economic welfare and well-being. For this analysis, the Selangor Zakat Authority (LZS-MAIS) is selected to present an example of governing zakat as a social institution in Malaysia.